The death of capital : how creative policy can restore stability - Lewitt, Michael E. (Hoboken, New Jersey : John Wiley & Sons, 2010)
A call for change that will create prolonged economic prosperity The Death of Capital discusses the phenomenon described as "the financialization of the U.S. economy" or how financial speculation came to dominate our economy at the expense of productive capital-resulting in an increasingly unstable economic base
1. The death of capital -- 2. Capital ideas -- 3. Empty promises -- 4. Financialization -- 5. From innovators to undertakers -- 6. Welcome to Jurassic Park -- 7. The road to hell -- 8. Finance after Armageddon -- 9. Conclusion: "This is later."
Includes bibliographical references (p. 279-286) and index
Keywords: Capital; Capitalism -- United States; Finance -- United States; Global Financial Crisis, 2008-2009